Factors affecting the travel mode choice of the urban elderly in healthcare activity: comparison between core area and suburban area. (January 2020) - Du, Mingyang; Cheng, Lin; Li, Xuefeng; Yang, Jingzong
Highlights: The healthcare travel behaviors of the elderly are different between core area and suburb in Fuzhou. The elderly in suburb are more likely to utilize cars to obtain high-quality medical resources. The service efficiency improvements of hospitals could promote the elderly in core area to choose green modes. For long-distance travel, the influence of family economic backgrounds on the mode choice is more significant in suburb. The elderly in core area are more inclined to utilize cars when they live with their offspring. Abstract: This study investigated the travel characteristics and influential factors of travel mode choice for healthcare activity by the elderly in core area and suburb. The results of descriptive analysis and multinomial logistic models show that: (1) Bus and walking are main modes for the elderly to seek medical treatment. The elderly in suburb travel longer distance and are more dependent on bus than those in core area. (2) The service efficiency improvements of hospitals could promote the elderly in core area to choose green modes, while those in suburb are more likely to utilize cars to obtain high-quality medical resources. (3) For long-distance travel, the influence of family economic backgrounds on the mode choice is more significant in suburb, and the difference of family economic will further aggravate the internal differentiation in long-distance travel among the elderly in suburb. (4) Interestingly, the elderly in core area tend to utilize cars to seek for healthcare when they live with their offspring, while those in suburb tend to use cars and taxis when they have serious illness and require companion. Finally, relevant policies and suggestions were proposed to improve the accessibility and fairness of healthcare travel for the elderly.